In situ observations of flux rope at the separatrix region of magnetic reconnection. Issue 1 (11th January 2016) - Huang, S. Y.; Retino, A.; Phan, T. D.; Daughton, W.; Vaivads, A.; Karimabadi, H.; Zhou, M.; Sahraoui, F.; Li, G. L.; Yuan, Z. G.; Deng, X. H.; Fu, H. S.; et al.
Abstract: We present the first in situ observations of a small‐scale flux rope locally formed at the separatrix region of magnetic reconnection without large guide field. Bidirectional electron beams (cold and hot beams) and density cavity accompanied by intense wave activity substantiate the crossing of the separatrix region. Density compression and one parallel electron beam are detected inside the flux rope. We suggest that this flux rope is locally generated at the separatrix region due to the tearing instability within the separatrix current layer. This observation sheds new light on the 3‐D picture of magnetic reconnection in space plasma. Key Points: Flux rope is observed at separatrix Flux rope is locally generated by tearing instability This observation sheds new light on the 3‐D picture of magnetic reconnection